Simulation Approaches in Transportation Analysis Recent Advances and Challenges - Kitamura, Ryuichi; Kuwahara, Maso.; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
SIMULATION APPROACHES IN TRANSPORTATION ANALYSIS: Recent Advances and Challenges focuses on the latest advanced research on modeling as well as applications of transport simulation, including simulation of vehicle movements on the road, dynamic simulation of traffic flow on transport networks, and simulation of the movement of people in an urban area. Models from the three continents of Europe, North America, and Asia are discussed in detail. Research issues and future directions of transport simulation development are systematically addressed. It is the first book to thoroughly discuss global developments and the broad issues of transport simulation. Moreover, transport simulation is recognized as the key concept in traffic control and demand management to achieve efficient, safe, and convenient urban transport system. SIMULATION APPROACHES IN TRANSPORTATION ANALYSIS: Recent Advances and Challenges will contribute to the development and application of transport simulation methods by: a) introducing state-of-the-art transport simulation models, methodologies, and examples of their applications, b) identifying short-term and long-term research issues, c) assessing promising application areas for simulation, and d) evaluating the applicability of transport simulation methods to other research areas. The book will be useful for researchers and graduate students to understand the application of simulation in transport analysis and future research needs. Practitioners will find the book useful for practical issues such as the applicability of simulation methods, their reproducibility, and output interpretation.
Simulation Models and Their Application: State of the Art -- Application of a Simulation-Based Dynamic Traffic Assignment Model -- The DRACULA Dynamic Network Microsimulation Model -- Dynamic Network Simulation with AIMSUN -- Microscopic Traffic Simulation: Models and Application -- Applications of Transport Simulation -- The Art of the Utilization of Traffic Simulation Models: How Do We Make Them Reliable Tools? -- Absorbing Markov Process OD Estimation and a Transportation Network Simulation Model -- Simulating Travel Behaviour using Location Positioning Data Collected with A Mobile Phone System -- Representing Traffic Dynamics -- Simulation of the Autobahn Traffic in North Rhine-Westphalia -- Data And Parking Simulation Models -- Saga of Traffic Simulation Models in Japan -- A Study on Feasibility of Integrating Probe Vehicle Data into A Traffic State Estimation Problem using Simulated Data -- Representing User Behavior -- Consistency of Traffic Simulation and Travel Behaviour Choice Theory -- Driver$1 (Bs Route Choice Behavior and its Implications on Network Simulation and Traffic Assignment -- An Overview of PCATS/DEBNetS Micro-simulation System: Its Development, Extension, and Application to Demand Forecasting.s
Keywords: Transportation; Operations research; Decision making; Computer simulation; Civil engineering; Industrial organization; Regional economics; Spatial economics; Economics; Regional/Spatial Science; Transportation; Civil Engineering; Simulation and Modeling; Operation Research/Decision Theory; Industrial Organization; Electronic books